„Szaman nigdy nie umiera”. Sztuka naskalna jako wyraz tożsamości w twórczości Jane Ash Poitras - Rozwadowski, Andrzej (Folia Praehistorica Posnaniensia, 2019)
This article discusses the phenomenon of reusing of ancient rock art iconography in modern art on the example of the artworks of Canadian Cree visual artist Jane Ash Poitras. To understand the role the rock art plays in the collages of J.A. Poitras, the first part of the paper is focused on the Indigenous perspective, which provides the clue to reading complexity of history and contemporary art of the First Nations in Canada. Then the painting Shaman never die V is thoroughly analyzed. It is showed that rock art motifs used in this artwork had been very carefully selected and the meanings they evoke significantly go in pair with wider ideas related to traumatic history of Indigenous Canadians as well as ideas related to persistence of Indigenous spirituality symbolized by the image of shaman.